(untitled) (Journal of the Management Sciences, 2025)
This study investigates the impact of customer journey mapping on e-commerce behaviors among millennials in Southeast Nigeria. The study explored how four critical dimensions—website usability, trust in digital payment systems, mobile responsiveness, and post-purchase support—shape millennials’ e-commerce behaviors in Southeast Nigeria, particularly their purchase decisions, satisfaction, retention, and loyalty. Data were collected via questionnaires distributed to millennials in select federal and state universities across Anambra, Enugu, and Imo states, achieving a 62% response rate. Using statistical analysis, the study found significant positive relationships between each journey element and corresponding consumer outcomes, underscoring the importance of a seamless, secure, and responsive digital shopping experience. The findings offer practical insights for e-commerce businesses seeking to enhance millennial engagement and competitiveness in Nigeria’s growing online market. Recommendations include improving website design, strengthening payment security, optimizing mobile platforms, and enhancing post-purchase services.